DISPERSE FERROMAGNET STRUCTURING IN MAGNETOVIBRATING LAYER - Yury M. Vernigorov; Ivan N. Egorov; Nikolay Y. Egorov (Advanced Engineering Research, 2010)
Structuring process features from electromagnetic field parameters are investigated by analyzing emf induction dependence induced by the ferromagnetic powder in the inductive sensor.